Knowledge and Attitudes Regarding Non‐Invasive Prenatal Testing (NIPT) and Preferences for Risk Information among High School Students in Sweden. Issue 3 (2nd August 2016) - Georgsson, Susanne; Sahlin, Ellika; Iwarsson, Moa; Nordenskjöld, Magnus; Gustavsson, Peter; Iwarsson, Erik
Abstract: Non‐invasive prenatal testing (NIPT) was recently introduced for prenatal testing of genetic disorders. Cell‐free fetal DNA is present in maternal blood during pregnancy and enables detection of fetal chromosome aberrations in a maternal blood sample. The public perspective to this new, simple method has not been illuminated. The views of young people (i.e. future parents) are important to develop suitable counseling strategies regarding prenatal testing. The aim was to explore Swedish high school students' attitudes, knowledge and preferences regarding NIPT. A questionnaire was completed by 305 students recruited from one high school in Stockholm, November and December 2014. Most students (80 %) considered prenatal testing as good. The majority (65 %) was positive or very positive towards NIPT and 62 % stated that they potentially would like to undergo the test if they or their partner was pregnant. The vast majority (94 %) requested further information about NIPT. Most students (61 %) preferred verbal information, whereas 20 % preferred information via the Internet. The majority of the high school students was positive towards prenatal testing and most was positive towards NIPT. Further, information was requested by the vast majority before making a decision about NIPT. Most of the students preferred verbal information and to a lesser extent information via the Internet. The attitudes, knowledge and preferences for risk information concerning NIPT in young adults are important, in order to increase knowledge on how to educate and inform future parents.